Cardiomyocyte Ultrastructure of Rats with Experimental Myocardial Infarction After Therapeutic Hypothermia and Mesenchymal Stromal Cell Administration - Trofimova, Anna V.; Chizh, Nikolay A.; Belochkina, Irina V.; Marchenko, Larisa N.; Govorukha, Tatuana P.; Repin, Nikolay V.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2017)
We studied the ultrastructural changes in cardiomyocytes during necrosis development and re-modelling of the rat heart following experimental myocardial infarction (MI) and performing therapeutic hypothermia and administration of allogeneic mesenchymal stromal cells (MSCs). The infarction was provoked via ligation of left coronary artery. Therapeutic hypothermia was performed in cold chamber for 60 min achieving 4Â°C skin temperature in the collar zone. The suspension of allogeneic cryopreserved MSCs of placenta with 1.2x10Â° cells/ml concentration was intravenously administered. In the animals with MI treated with MSCs and a combination of MSCs and hypothermia we revealed the normalization of mitochondrial structure, appearance of small dense mitochondria, the presence of a large number of glycogen granules, testifying thereby to a sufficient oxygen supply into cardiomyocytes and normalization of synthetic processes together with improved microcirculation under MSCs factors. The combination of therapeutic hypothermia with MSCs administration at the background of MI largely promoted the activation of compensatory-regenerative processes in cardiomyocytes. Probl Cryobiol Cryomed 2017; 27(4): 334-347